Legal Protection for Land Right Holders in the Event of Multiple Certificates - Ibnu Arly; Rinda Sara Afrilia (Budapest International Research and Critics University, 2021)
Land is the object that is most easily affected by disputes, whether disputes between individuals, individual disputes with legal entities, disputes between legal entities, even disputes involving the government, so that legal arrangements related to the control / granting of land rights must be maximized to ensure the protection of holders of land rights. land rights. In Government Regulation Number 24 of 1997 concerning Land Registration and as the basis for implementing regulations, PMA / Head of BPN Number 3 of 1997 concerning Provisions for Implementing Government Regulation Number 24 of 1997 concerning Land Registration are used. The implementation of land registration at the Land Office has fulfilled the principle of security as a form of embodiment of guarantees of legal certainty for holders of land rights. The form of the principle of security exists, both at the time of the implementation of the land registration itself and when a certificate has been issued, with the issuance of a certificate, the security guarantee for land rights has been attached to the holder of the land rights. The system used in land registration uses a negative system with a positive tendency, which means that the application of positive elements is also included in the negative system, so that a certificate can become the strongest and fullest right. Strength of proof against Land Office product certificates that have complied with the provisions of Article 32 of Government Regulation Number 24 of 1997. In Indonesia, land rights certificates act as strong evidence as confirmed in Article 19 paragraph (2) letter c of the UUPA and Article 32 paragraph (1) Government Regulation Number 24 of 1997 concerning land registration, which has now been revoked and reaffirmed in Government Regulation Number 24 of 1997.